Variation of Mineral Concentrations Among Different Potato Varieties Grown at Two Distinct Locations in Ethiopia - Abebe, Tesfaye; Wongchaochant, Shermarl; Taychasinpitak, Thunya; Leelapon, Oranuch (Agriculture and Natural Resources, 2012)
The extent of genetic variation in the protein and ﬁ ber contents and the iron (Fe), zinc (Zn) and phosphorus (P) concentrations of 21 different potato varieties was studied at two distinct locations in Ethiopia. The experiments were conducted in a randomized complete block design in triplicate. Analysis of variance (ANOVA) of each set of experimental data revealed signiﬁ cant (P < 0.01) genetic variation among varieties. The combined ANOVA also showed signiﬁ cant (P < 0.01) variation due to location and genotype × location interactions. Accordingly, the tuber protein and ﬁ ber contents ranged from 3.77 to 7.36% and 1.18 to 2.07%, respectively. Likewise, the Fe, Zn and P concentrations ranged from 17.13 to 164.83, 7.07 to 20.21 and 143.68 to 357.76 mg.kg-1 dry weight, respectively. Consequently, men, women, and children can get 29, 13.3 and 65%, respectively, of their daily recommended nutrient intake (RNI) of Fe from eating 200 g fresh weight of tubers of the high Fe concentration variety Sisay and 12, 14.3 and 17%, respectively, of their daily RNI of Zn from 200 g of tuber of the high Zn variety Menagesha. Correlation analysis indicated a signiﬁ cant (P < 0.01) association among these characters but not with protein and ﬁ ber with Fe. Thus, this study found considerable variation in the mineral concentrations among potato varieties in Ethiopia which can be useful information to help curb mineral malnutrition.